SHARIA-BASED MARKETING STRATEGIES FOR INCREASING HOUSING SALES IN THE CITY OF TASIKMALAYA - Ramdan Hidayat; Eggy Armand Ramdani; Tazkiyah Ainul Qolbi (Syari'ah Economics, 2022)
Marketing strategy is an essential component of any business operation. Whether a business is successful depends on whether its marketing strategy is effective for its needs. Therefore, the selection of a marketing strategy requires precise calculations and analysis. According to the title observed, the method used in this study is a qualitative research method that generates descriptive data through observations, interviews, and documentaries. Cordova Living is a housing community that employs a sharia payment system, eliminating the BI checking system so that there are no interest, usury, confiscation, or fines. Based on the fact that Cordova Living was the pioneer of sharia-compliant housing in Tasikmalaya, the sharia marketing strategy is a great fit for marketing its products. As evidenced by the marketing mix, implementing sharia marketing strategies can increase sales figures and the selling value of Cordova Living housing. In terms of price (price) has advantages for consumers to negotiate because of the khiyar rights. In terms of products, transparency from start to finish, detailed explanations, and the freedom to bargain and negotiate can eliminate the element of fraud. The strategic place (location) close to the city center and education center provides added value for Cordova Living. The promotion (promotion) used by Cordova Living is friendly and applies 3S (senyum/smiles, salam/greetings, and sapa/greetings) and friendly service by applying Islamic rules.